WEB-BASED RAW MATERIAL OR SUPPLIER SUPPLY REPORT SYSTEM SHOP VINNY KITCHEN MDO - Frizal Marlissa; Ai Rosita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Kitchen Store Mdo means a figure engaged in the electrical component manufacturing industry, namely circuit breakers Breakers ). Vinny's Kitchen Store Mdo depends on consumer orders, for the production process it takes 1 week. at Vinny's Kitchen Store Mdo has a number of dilemmas, namely, PPIC officers plan the procurement of raw materials based on intuition / estimates only as a result it is not uncommon for shortages and excesses of standard materials to occur, If the shortage results it can slow down the production process, and lead to inaccurate targets when sending to customers, and If excess will have an impact on high storage costs and the risk of loss and damage to standard materials. Based on the problem of the availability of standard material stocks and problems related to updating warehouse inventory data and data consistency, it can be solved using the MRP (Material Requirements Plan) method in the form of web-based computer software. the hope of using this application is that there will be an increase in effectiveness and efficiency, as well as timeliness in delivery to consumers can be fulfilled which will lead to an increase in Character profits.